Membangun Hubungan Jangka Panjang Pelanggan Melalui Relationship Marketing - Rully Arlan Tjahyadi (Universitas Kristen Maranatha, 2006)
Relationship marketing, however defined, has received considerable attention recently. Relationship marketing has emerged as a new paradigm in the marketing’s concepts and practices. This paradigm has shifted from transactional approach to relationship-based marketing strategy. The main purpose of relationship marketing is focused on a long-term relationship with a key parties—customer, suppliers, and distributor. Today, relationship marketing concept has been a key point of firm’s business activities. In a modern business, marketer’s tasks not only meet customer want, but also treat their customer as well. Firm should understand the principles of underlying relationship marketing before. Those principles are loyalty and customer satisfaction, profitability, and customer retention. Relationship marketing is concerned with how organizations manage and improve their relationships with customer for long-term profitability. In the end of this paper, I will define important steps that marketers must do. Finally, this paper discusses about relationship marketing in building relationship with customer for long-term.